Alchemizing earth's legacy: Bismuth-engineered humic nanoparticles for IBD theranostics through mitochondrial anti-inflammation and sustained intestinal delivery - Ganglin Wang; Ziwei Wang; Lin Liu; Yejing Zhu; Jiali Zhong; Jiayi Zhang; Lingling Wang; Chenguo Zheng; Wei Li (Materials Today Bio)
Humic acid (HA), a complex organic substance naturally present in soil, peat, and coal, is traditionally referred to as the extract of ''Wujinshi'' (乌金石) in Chinese medicine. It is renowned for its potent anti-inflammatory, analgesic, and blood circulation-promoting properties. However, its mechanisms and delivery methods require further exploration. We developed BiHANs, a novel nanoparticle combining bismuth and HA, which exhibits excellent biocompatibility and anti-inflammatory effects in vitro. Orally administered BiHANs accumulate at inflammatory sites in the colon of DSS-induced IBD mice, as confirmed by CT imaging, and prolong intestinal retention. They significantly alleviate acute and chronic intestinal damage by suppressing inflammatory responses, modulating gut microbiota, and targeting macrophage mitochondria to inhibit NF-κB-driven cytokine production. BiHANs also maintain mitochondrial homeostasis and exert antioxidative effects. Furthermore, their performance in CT imaging highlights potential as a theranostic agent. This study demonstrates BiHANs as a promising platform for targeted IBD therapy and diagnosis, combining anti-inflammatory efficacy with imaging capabilities.